PENGARUH KOMPENSASI, MOTIVASI DAN LINGKUNGAN KERJA MELALUI KEPUASAN KERJA TERHADAP EFEKTIVITAS KERJA TENAGA KEPENDIDIKAN KONTRAK KERJA DI UNIVERSITAS JEMBER - Sugianto, Sugianto (BISMA: Jurnal Bisnis dan Manajemen, 2018)
Abstract: University of Jember (UNEJ) is the only state university in Jember Regency under the Ministry of Research, Technology, and Higher Education of Republic of Indonesia. The administration staffs, especially the temporary educational staffs, have a significant role in performing administration service to support the educational system of the university. The objective of this research is to significantly examine the direct influence of compensation, motivation, and work environment on work effectiveness and indirect influence of compensation, motivation, and work environment on work effectiveness through work satisfaction. This is an explanatory quantitative research with the sample consisted of 180 temporary educational staff at University of Jember. Data were analyzed using Structural Equation Modelling (SEM). Results show that compensation has a positive and significant influence on job satisfaction and work effectiveness; motivation has a positive and significant influence on job satisfaction and work effectiveness; work environment has a positive and significant influence on job satisfaction and work effectiveness; and job satisfaction has a positive and significant influence on work effectiveness. Keywords: Compensation, Motivation, Work Environment, Work Satisfaction, and Work Effectiveness.